Éco-graphies - Prince, Nathalie,Thiltges, Sébastian (Presses universitaires de Rennes, 2018)
La 4e de couverture indique :
Includes bibliographical references and index
Keywords: Human ecology / Juvenile literature; Human ecology in literature; Environmentalism in literature; Children's literature / 20th century / History and criticism; Children's literature / 21st century / History and criticism; Children's literature; Écologie humaine dans la littérature; Environnementalisme dans la littérature; Littérature de jeunesse / 20e siècle / Histoire et critique; Littérature de jeunesse / 21e siècle / Histoire et critique; Kinderliteratur; Jugendliteratur; Umweltschutz; Humanökologie